Finerenone attenuates myocardial apoptosis, metabolic disturbance and myocardial fibrosis in type 2 diabetes mellitus - Tao Jin; Xiangrui Fu; Ming Liu; Fengshuang An (Diabetology & Metabolic Syndrome, 2023)
Abstract Background Finerenone is a third-generation mineralocorticoid receptor antagonists, which has shown good cardiac function improvement in patients with type 2 diabetes in large-scale clinical trials. However, its specific role in diabetic cardiomyopathy remains unclear. We explored the potential functions and mechanisms of finerenone in diabetic cardiomyopathy. Methods The type 2 diabetic rat model was induced by high-fat diet and low-dose streptozotocin (n = 6, each group). Next the drug group was treated with finerenone (1 mg/kg/day) for 8 weeks. Then we detected the cardiac structure and function and relevant indicators. Neonatal rat cardiomyocytes were used for in vitro culture to determine the direct effect of finerenone on cardiomyocytes stimulated by high glucose and high fatty acid. Results Compared with the control group, rats in the type 2 diabetes group exhibited hyperglycemia, hyperlipidemia, and impaired cardiac function. Myocardium showed increased fibrosis and apoptosis. Finerenone attenuated these impairments without changing blood glucose levels. In neonatal rat cardiomyocytes, the stimulation of high concentrations of palmitic acid increased fatty acid uptake, as well as increased reactive oxygen species and apoptosis. Finerenone significantly improved fatty acid metabolism, reduced cellular inflammation levels, and decreased apoptosis. Conclusions By blocking the mineralocorticoid receptor, finerenone attenuates cardiac steatosis, myocardial fibrosis and apoptosis, and subsequent myocardial remodeling and diastolic dysfunction in type II diabetic rats.